2004
DOI: 10.1248/bpb.27.879
|View full text |Cite
|
Sign up to set email alerts
|

Suppressed Permeation of Linoleic Acid in a Liposomal Formulation through Reconstructed Skin Tissue

Abstract: Since the liposomal formulation of linoleic acid (LA) exhibited an enhanced skin-whitening effect, the influence of liposomalization on the cutaneous absorption of LA was examined using a three-dimensional (3D) reconstructed skin model. Liposome entrapped [ 14 C]-LA was applied on the skin model, and the permeation of LA through the skin was monitored. The permeation rate of LA in the liposomal formulation was found to be lower than that in the conventional formulation without liposomes, suggesting the increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…However, empty DL1 and DL2, as controls, showed no whitening effect . These results suggested that deformable liposomes enhanced whitening efficacy by fusing with the lipid bilayer of cellular membranes, entrapping agents in the cells for a long period of time . We proposed the following mechanism to explain why DL2 exerted a higher whitening effect than DL1: 1) DL2 contained higher amount of edge activator than DL1, which loosened the cell membrane structure, enabling the liposomes to fuse with the cell membranes; 2) MP concentration in DL2 was higher than that in DL1, which increased the whitening effect.…”
Section: Resultsmentioning
confidence: 99%
“…However, empty DL1 and DL2, as controls, showed no whitening effect . These results suggested that deformable liposomes enhanced whitening efficacy by fusing with the lipid bilayer of cellular membranes, entrapping agents in the cells for a long period of time . We proposed the following mechanism to explain why DL2 exerted a higher whitening effect than DL1: 1) DL2 contained higher amount of edge activator than DL1, which loosened the cell membrane structure, enabling the liposomes to fuse with the cell membranes; 2) MP concentration in DL2 was higher than that in DL1, which increased the whitening effect.…”
Section: Resultsmentioning
confidence: 99%
“…The three-dimensional cultured skin model is valuable for dermatological research as an in vitro model for assessing the pharmacological potency, toxicity and metabolism of tested compounds because of its similarity to actual human skin having the interaction between dermis and epidermis (Bernerd and Asselineau, 2008, Duval et al, 2003, Shigeta et al, 2004. UVB radiation can increase melanin biosynthesis and proliferation of melanocytes in the epidermis by acting on melanocytes directly (Friedmann and Gilchrest, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Currently in the literature a wide range of therapeutic properties of CLA is described including prevention of osteoporosis , supporting of immune system , reduction of atherosclerosis risk , reducing of body fat deposition and stimulating the building of muscle mass . Non‐conjugated linoleic acid (LA) was also reported as a potential therapeutic agent to treat melasma disorders and in skin whitening . Unfortunately, linoleic acid is quite vulnerable to oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…In the attempt to suppress the oxidation process conventional and ultradeformable liposomes were proposed as drug delivery systems. Experimental data revealed that liposomal formulations increased the incorporation of the drug into the melanocytes and suppressed the synthesis of melanin and therefore enhanced the skin‐whitening effect of LA .…”
Section: Introductionmentioning
confidence: 99%